To combine the two transformations applied to the triangle \( ΔABC \), we need to analyze each transformation step-by-step and then combine them into one rule.
First Transformation
The first transformation is given by the rule:
\[ (x, y) \rightarrow (x + 4, y - 6) \]
Let's apply this transformation to each vertex of triangle \( ABC \):
-
A(-8, 4): \[ A' = (-8 + 4, 4 - 6) = (-4, -2) \]
-
B(-5, 8): \[ B' = (-5 + 4, 8 - 6) = (-1, 2) \]
-
C(-3, 3): \[ C' = (-3 + 4, 3 - 6) = (1, -3) \]
Thus, after the first transformation, the coordinates of triangle \( A'B'C' \) are: \[ A'(-4, -2), \quad B'(-1, 2), \quad C'(1, -3) \]
Second Transformation
The second transformation is given by the rule:
\[ (x, y) \rightarrow (x + 5, y - 3) \]
Now we apply this transformation to each vertex of triangle \( A'B'C' \):
-
A'(-4, -2): \[ A'' = (-4 + 5, -2 - 3) = (1, -5) \]
-
B'(-1, 2): \[ B'' = (-1 + 5, 2 - 3) = (4, -1) \]
-
C'(1, -3): \[ C'' = (1 + 5, -3 - 3) = (6, -6) \]
Thus, after the second transformation, the coordinates of triangle \( A''B''C'' \) are: \[ A''(1, -5), \quad B''(4, -1), \quad C''(6, -6) \]
Combined Transformation Rule
We can combine the two transformations first. We know that:
- The first transformation moves any point \((x, y)\) to \((x + 4, y - 6)\).
- The second transformation moves \((x, y)\) to \((x + 5, y - 3)\).
If we consider the combination directly, we add both transformations together:
-
For the \(x\)-coordinate: \[ x \rightarrow x + 4 \rightarrow (x + 4) + 5 = x + 9 \]
-
For the \(y\)-coordinate: \[ y \rightarrow y - 6 \rightarrow (y - 6) - 3 = y - 9 \]
Thus, the new combined rule is:
\[ (x, y) \rightarrow (x + 9, y - 9) \]
Final Coordinates
Using the final combined rule, if we were to apply it to the original triangle \( ΔABC \) or any point \((x, y)\):
For the original vertices:
-
A(-8, 4): \[ A'' = (-8 + 9, 4 - 9) = (1, -5) \]
-
B(-5, 8): \[ B'' = (-5 + 9, 8 - 9) = (4, -1) \]
-
C(-3, 3): \[ C'' = (-3 + 9, 3 - 9) = (6, -6) \]
Conclusion
The coordinates of triangle \( ΔA''B''C'' \) are:
\[ A''(1, -5), \quad B''(4, -1), \quad C''(6, -6) \]